Occupational Stress Among Nurses in UAE-Based Healthcare Facilities (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Nurses in the United Arab Emirates (UAE) encounter unique occupational stressors. This study aimed to assess the stress among nurses in UAE healthcare facilities and examine related factors. Methods: A cross-sectional survey was conducted involving 85 nurses. Data were collected on demographics, compassion satisfaction, burnout, and secondary traumatic stress using validated scales. Descriptive statistical analyses were performed. Results: The total score for Compassion Satisfaction was 12980 (Mean=32.37, SD=6.56, median=33). The Burnout Scale's total score was 13468 (Mean=36.03, SD=7.58, median=37). Finally the total secondary trauma scale was 8107 (Mean=15.72, SD=6.78, median=15). Finally, the analysis found that compassion satisfaction correlated was (6.557220842). Conclusion: Results indicate high levels of job satisfaction and highlight the critical need for interventions and well-being. Further research with larger samples and longitudinal designs is needed.